2012
DOI: 10.1007/s11695-012-0746-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Sleeve Gastrectomy: Symptoms of Gastroesophageal Reflux can be Reduced by Changes in Surgical Technique

Abstract: BackgroundBariatric surgery is the most effective treatment for gastro-esophageal reflux disease (GERD) in obese patients, with the Roux-en-Y gastric bypass being the technique preferred by many surgeons. Published data reporting the results of laparoscopic sleeve gastrectomy (LSG) in patients with GERD are contradictory. In a previous observational study, we found that relative narrowing of the distal sleeve, hiatal hernia (HH), and dilation of the fundus predispose to GERD after LSG. In this study, we evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(99 citation statements)
references
References 19 publications
(27 reference statements)
2
86
0
3
Order By: Relevance
“…There are studies in the literature reporting that reflux symptoms got worse after surgery in patients not treated for an existing hiatal hernia during SG [16]. In a study of Daes et al, it was found that hiatal hernia was intraoperatively detected in 25% of patients undergoing SG and that reflux symptoms decreased significantly after HHR [17]. In our study, this rate was found to be 80%.…”
Section: Discussionsupporting
confidence: 49%
“…There are studies in the literature reporting that reflux symptoms got worse after surgery in patients not treated for an existing hiatal hernia during SG [16]. In a study of Daes et al, it was found that hiatal hernia was intraoperatively detected in 25% of patients undergoing SG and that reflux symptoms decreased significantly after HHR [17]. In our study, this rate was found to be 80%.…”
Section: Discussionsupporting
confidence: 49%
“…Other patients develop de novo GERD after surgery [42,43]. In a concurrent cohort study carried out by Daes et al [44], 134 patients with (49.2%) or without preexisting GERD (50.8%) received LSG and were followed for 12 months. Only 1.5% had symptoms of GERD after one year.…”
Section: Long-term Resultsmentioning
confidence: 99%
“…Bei Kravetz et al [11] [15,26]. Die Torsion des Schlauches infolge einer Variation des Abstands zwischen kleiner Magenkurvatur und Klammernahtreihe kann zu einer Long-segment-Stenose führen [3]. Weitere Ursachen für Spätstenosen sind narbig ausgeheilte Leckagen und Fistelungen (.…”
Section: Epidemiologieunclassified